PENGARUH PENERAPAN TEKNIK THINKING ALOUD PAIR PROBLEM SOLVING (TAPPS) DISERTAI LEMBAR KERJA SISWA (LKS) TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA KELAS VIII SMPN 2 RAO KABUPATEN PASAMAN TIMUR - Ajir, Siti; Haryono, Yulia; Yuliana Fitri, Dewi (STKIP PGRI Sumbar, 2014)
ABSTRACTThis research was done based on the ract which indicated the low students ability in solving mathematic questions. Then,the students did not want to share each other. The purpose of this research was to know whether the VIII grade students of SMPN 2 East Pasaman Rao treated by Thinking Aloud Pair Problem Solving (TAPPS) technique and students worksheet have better mathematic problem solving than those who are treated by conventional learning. This was an experimental reserach which used random sampling.The instrument was problem solving test. The hypothesis was tested by one tailed test by using MINITAB.Â Hipotesis test result obtained p-value = 0,000. It was found that the hypothesis was accepted. Thus,it can be concluded that the students treated by Thinking Aloud Pair Problem Solving (TAPPS) and students worksheet had better mathematic problem solving than those who treated the conventional learning.